(untitled) (Ukrainian Journal of Ophthalmology, 2025)
This paper reports a case of recurrent toxoplasmic chorioretinitis in a patient with cellular immunodeficiency. A 37-year-old male presented to an ophthalmologist with complaints of reduced visual acuity and discomfort in his left eye. He had a history of at least two episodes of acute posterior uveitis without identifying the cause of inflammation. An ophthalmoscopic evaluation revealed a scar in the right retina and signs of acute vitritis and chorioretintis surrounding a scar in the left retina. Paired serology confirmed a diagnosis of toxoplasmosis. A deficiency of NK T-cells and cytotoxic СD8+ T-cells was noted, but there was no evidence of secondary immunosuppression. The Primary Immunodeficiency (PID) panel providing sequencing of 208 genes did not find a disease. A test for genetic folate cycle deficiency was conducted due to persistent hyperhomocysteinemia. The genetic testing identified two pathogenic polymorphisms in the genes coding for folic acid cycle enzymes (heterozygous MTHFR A1298C and homozygous MTRR A66G), which was believed to be associated with a cellular immunity, taking into account the data on immunosuppression and opportunistic infections in the presence of a genetic folate cycle deficiency. The following treatment was administered: spiramycin, 3.0 mln units orally daily for 14 days, to inhibit toxoplasma; recombinant human alpha2 interferon (3.0 mln units intramuscularly every other day for a month) and oxodihydroacridinylacetate sodium 2.0 mln units intramuscularly every other day for a month, with switching between this agent and interferon, to compensate for a deficiency of NK T-cells and СD8+ T-cells; and daily peribulbar injection of betamethasone 4 mg/mL for 3 days. The first signs of improved visual acuity were seen at day 8, and a complete restoration of vision in the left eye was achieved by the end of one month of combination therapy. In addition, the patient received three one-month courses of alpha2 interferon for compensation of cellular immunodeficiency over two years which prevented a recurrence of toxoplasmosis.